2011
DOI: 10.1007/s10530-011-0122-8
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific displacement mechanisms by the invasive little fire ant Wasmannia auropunctata

Abstract: Competition between invasive species and native ones in the new environment was found to be significant and to affect both animal and plant species. Invasive ants are notorious for displacing local ant species through competition. Competitive displacement of native species can occur through interference and or resource competition. However, for invasive ants, little is known about the relative importance of competitive displacement. We studied competitive interactions of the little fire ant, Wasmannia auropunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…While these studies shed considerable light on invasion processes, we lack similar detailed studies of other exotic ant species, in particular W. auropunctata , between their native and introduced home range (McGlynn, ). Recent work by Vonshak, Dayan, and Hefetz () investigated the competitive interactions between W. auropunctata and native ant species in a laboratory setting. They found that over a short time span (2 hr), W. auropunctata had the poorest foraging abilities (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these studies shed considerable light on invasion processes, we lack similar detailed studies of other exotic ant species, in particular W. auropunctata , between their native and introduced home range (McGlynn, ). Recent work by Vonshak, Dayan, and Hefetz () investigated the competitive interactions between W. auropunctata and native ant species in a laboratory setting. They found that over a short time span (2 hr), W. auropunctata had the poorest foraging abilities (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…time to discovering, retrieving and defending resources) when worker densities were low. However, over 21 days W. auropunctata rebounded and displaced the other ant species by raiding their nests (Vonshak et al., ). One explanation is that W. auropunctata behaves as an “insinuator” species, in which workers do not display aggression at low worker densities enabling them to forage undetected alongside dominant ant species.…”
Section: Discussionmentioning
confidence: 99%
“…Even with W. auropunctata data points removed, habitat type remained an important factor for colony growth rate (F 2,160 ϭ 4.853; P ϭ 0.009). Although several mechanisms might explain how W. auropunctata may have limited growth of other ant species within the high-shade coffee, one recent study points to a potential mechanism whereby W. auropunctata invade nests of other species and consume their workers and brood (Vonshak et al 2012). Thus, W. auropunctata may have preyed on individuals of other species, leading to increased colony growth after other ants harvested added food.…”
Section: Discussionmentioning
confidence: 99%
“…Numeric dominance has been cited in numerous studies on invasive ants as the most important factor promoting the success of these ants (Holway et al, 2002a;O'Dowd et al, 2003;Abbott et al, 2007;Rowles & O'Dowd, 2007;Vonshak et al, 2012). However, invasive ant species first arrive within a recipient environment as small propagules and do not have this numeric dominance (Hee et al, 2000;Holway et al, 2002a;Tillberg et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies are largely based on bait sampling and generalisations with regards to biological characteristics of invasive ants as measures to predict invasion success (Holway, 1999;Richardson et al, 2000;Holway et al, 2002b). However, detailed studies on the direct interactions between native ants and invasive ants are wanting, and are needed to understand how invasive ant species colonise new environments and which of their biological traits are likely to enhance their invasion success (Blight et al, 2010;Vonshak et al, 2012). For L. humile, the combination between abiotic conditions and inter-specific competition from native ant species may limit the extent to which these ants invade new environments as small propagules, largely because niche availability and suitability is determined by abiotic factors as well as the presence of competitive dominant ant species (Holway, 1999;Thomas & Holway, 2005;Walters & Mackay, 2005).…”
Section: Introductionmentioning
confidence: 99%